Investigation of the Optoelectronic Performance of GaAs Nanostructures for Solar Cell Applications. (December 2022) - Tenwar, Ankit Kumar; Singh, Sadhna; Prashant, D.V.; Samajdar, Dip Prakash
Abstract: In this article, we have performed a comprehensive comparative analysis of the optoelectronic performance of five different GaAs based nanostructures namely cylindrical nanowire (CNW), truncated nanocone (TNC), hexagonal nanowire (HNW), truncated nanopyramid (TNP) and rectangular nanowire (RNW). These nanostructures can improve the photon harvesting capability and the absorption characteristics of the devices. The optical absorptance, optical Jsc, electric field and photogeneration rates of GaAs based nanostructures are computed using Wave Optics Module of the commercially available COMSOL Multiphysics package. The electrical performance of these nanostructures obtained in the form of J-V characteristics is analysed using the Semiconductor Module. The important geometrical parameters of the nanostructures such as period (P), diameter (D), Width (W), bottom W and D (Wbot /Dbot ), top W and D (Wtop /Dtop ), and filling ratio (FR) are varied in order to have a deep level understanding of the effect of the geometry of the nanostructures on their optical performance. The surface recombination velocity (SRV) of the p and n regions of the active material is varied to find out the impact on the electrical performance of the investigated nanostructures. We observed that the optical characteristics of the nanostructures are dependent on the geometrical dimensions, whereas the electrical characteristics depend substantially on the recombination mechanisms. Graphical Abstract: ga1 Highlights: Finite Element Method based Analysis of different GaAs nanostructures performed. The effect of the geometrical parameters of the nanostructures on optical performance studied. Electrical performance analysis of the nanostructures done using Semiconductor Module. The effect of surface recombination velocity on photovoltaic performance studied.